Analysis Of Children's Independence Through Habitative Activities At Dewi Kayangan Kindergarten In The 2024/2025 Academic Year - Sari, Ratna Komala; Habiburrahman, Lalu; Mahendra, Juandra Prisma (Lembaga Penelitian dan Pendidikan Mandala, 2025)
Abstract. The habituation method aims to help children display the best behavior in their daily lives, both habituation in the school environment and in the family environment and in the community. The author's focus on children's independence through habituation activities at Dewi Kayangan Kindergarten inspired this research. This research at Dewi Kayangan Kindergarten focuses on how to analyze children's independence through habituation activities in class A kindergarten. There are three approaches taken in this research: observation, interviews, and documentation. this type of research is qualitative descriptive. While data analysis is carried out through analysis before being in the field, analysis during being in the field, data analysis during being in the field. Test the validity of data through triangulation and member checks. The results showed that: (1) children's independence activities through habituation activities at Dewi Kayangan Kindergarten are carried out every day with routine activities, weekly activities, and monthly activities (2) Factors that influence the success of developing independence are influenced by the role of teachers, parental involvement, infrastructure and educational game tools.